0 mehakNewbie Asked: June 14, 20232023-06-14T15:20:23+05:30 2023-06-14T15:20:23+05:30In: CBSE If α and β are the zeros of the quadratic polynomial p(x) = 4×2 – 5x – 1, find the value of α2β+αβ2. 0 why is this formula used here? What will be the answer of α2β+αβ2 when the quadratic polynomial used is p(x) = 4×2 – 5x – 1. Class 10th mathematics chapter 2nd. polynomials class 10thrd sharma mathematics Share Facebook 1 Answer Voted Oldest Recent [Deleted User] 2023-09-27T13:57:46+05:30Added an answer on September 27, 2023 at 1:57 pm Solution: From the question, it’s given that: α and β are the roots of the quadratic polynomial p(x) where a = 4, b = -5 and c = -1 So, we can find Sum of the roots = α+β = -b/a = – (-5)/4 = 5/4 Product of the roots = αβ = c/a = -1/4 To find, α^{2}β+αβ^{2} ⇒ αβ(α +β) ⇒ (-1/4)(5/4) = -5/16 0 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment. Related Questions 15. The angle of elevation of the top of a tower as observed from a point in a ... 14. The angle of elevation of a tower from a point on the same level as the foot ... 13. On the same side of a tower, two objects are located. When observed from the top of ... 12. A parachute is descending vertically and makes angles of elevation of 45° and 60° at two observing ... 11. The shadow of a tower, when the angle of elevation of the sun is 45°, is found ...

Solution:From the question, it’s given that:

α and β are the roots of the quadratic polynomial p(x) where a = 4, b = -5 and c = -1

So, we can find

Sum of the roots = α+β = -b/a = – (-5)/4 = 5/4

Product of the roots = αβ = c/a = -1/4

To find, α

^{2}β+αβ^{2}⇒ αβ(α +β)

⇒ (-1/4)(5/4) = -5/16